2022
DOI: 10.3390/nano12234111
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Photocatalytic Degradation Pathways and Mechanism of Tetracycline by an Efficient Z-Scheme NiFe-LDH/CTF-1 Heterojunction

Abstract: Photocatalysis offers a sustainable approach for recalcitrant organic pollutants degradation, yet it is still challenging to seek robust photocatalysts for application purposes. Herein, a novel NiFe layered double hydroxide (LDH)/covalent triazine framework (CTF-1) Z-scheme heterojunction photocatalyst was rationally designed for antibiotics degradation under visible light irradiation. The NiFe-LDH/CTF-1 nanocomposites were readily obtained via in situ loading of NiFe-LDH on CTF-1 through covalent linking. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Attributing to the successive action of • OH radical and other ROS, T1 undergoes further dehydration, yielding T2 ( m / z = 410) . In a parallel manner, deamination as well as N -demethylation by primary oxidants (i.e., • OH and • O 2 – ) can also transform TC to T3 ( m / z = 396) . On subsequent oxidation by holes and the multiple ROS synchronously generated, these intermediates (i.e., T2 and T3 ) are converted to T4 ( m / z = 318), T5 ( m / z = 302), and T6 ( m / z = 274), primarily through ring-opening reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attributing to the successive action of • OH radical and other ROS, T1 undergoes further dehydration, yielding T2 ( m / z = 410) . In a parallel manner, deamination as well as N -demethylation by primary oxidants (i.e., • OH and • O 2 – ) can also transform TC to T3 ( m / z = 396) . On subsequent oxidation by holes and the multiple ROS synchronously generated, these intermediates (i.e., T2 and T3 ) are converted to T4 ( m / z = 318), T5 ( m / z = 302), and T6 ( m / z = 274), primarily through ring-opening reactions.…”
Section: Resultsmentioning
confidence: 99%
“…59 In a parallel manner, deamination as well as Ndemethylation by primary oxidants (i.e., • OH and • O 2 − ) can also transform TC to T3 (m/z = 396). 60 On subsequent oxidation by holes and the multiple ROS synchronously generated, these intermediates (i.e., T2 and T3) are converted to T4 (m/z = 318), T5 (m/z = 302), and T6 (m/z = 274), primarily through ring-opening reactions. As the reaction progresses, all the fragmentation compounds are ultimately dissociated into low-molecular-weight hydrocarbons and other ring-scission products, such as T7 (m/z = 109) and T8 (m/z = 148), and thereafter gradually mineralized to CO 2 , H 2 O, NH 4 + , and NO 3 − .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Various types of semiconductor–semiconductor heterojunctions exist, including type-I (straddling gap), type-II (staggered gap), type-III (broken gap), Z-scheme, n–p, p–p, and n–n heterojunctions. 161 Among them, type-II 162 and Z-scheme 163 heterojunctions are commonly formed structures when combining CTFs with other semiconductor materials (Table 3).…”
Section: Strategies For Improving the Photocatalytic Activity Of Ctfsmentioning
confidence: 99%
“…Further, it has been reported that photocatalytic degradation can be improved by utilizing nanomaterials, nanocomposites, or nanostructures. Nanomaterials for photodegradation must feature an appropriate bandgap (~3 eV), controllable electron-hole recombination rates, electrical conductivity, and corrosion resistance [178][179][180]. In that regard, photodegradation assisted by semiconductor nanomaterials or nanocomposites is promising because of their charge separation and ability to effectively absorb light in the visible region.…”
Section: Nanomaterials For the Photodegradation Of Pollutantsmentioning
confidence: 99%